The fine structure of starch: a review - Chen Zhiguang; Zhong Haixia; Chen Min; Gong Fayong; Li Jing (npj Science of Food)
Abstract Starch is an important renewable resource in nature. In this paper, the recent research advances in starch structure were systematically summarized from the granular and molecular levels. Meanwhile, the changes in starch multi-scale structures under different conditions were discussed. Furthermore, we redefine the growth ring structure of starch granule, and postulate a model for the fine structure of starch granule. It may provide important insights for the research of starch.